The visibility of smoking in Europe and its relationship with youth’s positive beliefs about smoking - Lagerweij, Naomi A. (2019)
Objectives: To determine adolescent-reported visibility of smoking in different public and private spaces in Europe and associations between smoking visibility and beliefs about the benefits of smoking. Methods: We used SILNE-R cross-sectional survey data (2016/2017) of 10,798 14–16-year-old students from 55 secondary schools in seven European cities. Respondents reported for private and public spaces whether they had seen others smoke there in the last 6 months. Beliefs about the benefits of smoking were measured on a 7-item scale; higher scores indicated more positive beliefs. Multilevel linear regression analyses determined associations while controlling for potential confounders and stratifying by smoking status. Results: Most students reported observing others smoke in public spaces, especially at train/bus stations (84%). Positive beliefs about smoking of never smokers were positively associated with seeing others smoke in train/bus stations and leisure/sports facilities, but not at home, a friend’s home, restaurants or bars, when fully adjusted. Associations were of similar magnitude for ever smokers. Conclusions: Smoking in several public places is highly visible to adolescents. Reducing this visibility might weaken positive beliefs that adolescents have about smoking.